REAL-TIME PCR TECHNOLOGY FOR CATTLE GENOTYPING BY A AND B KAPPA-CASEIN GENE ALLELES - R. R. Vafin; Kh. Kh. Gilmanov (Academic Scientific Journal of Chemistry, 2021)
The main goal of the study was to develop and test an effective technology for cattle genotyping by the CSN3 gene based on real-time PCR with hybridization-fluorescence detection. There was developed a method for real-time PCR for cattle genotyping by A and B alleles of the CSN3 gene in the format of hybridization-fluorescence detection, involving the use of two 5/ -fluorescence-labeled forward allele-specific primers, one reverse common primer, and one anti-primer labeled with a fluorescence quencher at the 3/ -end of the oligonucleotide. As a result of practical studies aimed at testing the developed method, we obtained the technical result provided by the proposed technology, expressed in the effective identification of the desired genotypes due to correct interpretation of these curves of increasing fluorescence intensity, the results reliability of which was also confirmed by the well-known PCR-RFLP analysis technique for Bos taurus genotyping for similar allelic variants of the kappa-casein gene